Optical burst switching a viable solution for terabit IP backbone. - Verma, S. (IEEE Network : the magazine of global information exchange)
Wavelength-division multiplexing has emerged as an important physical layer technology. Optical transmission provides a physical layer capable of carrying bits at the speed at the order of a gigabit per second. Optical burst switching is proposed to overcome the shortcomings of conventional WDM deployment, such as lack of fine bandwidth granularity in wavelength routing and electronic speed bottlenecks in SONET/SDH. We describe an architecture for IP network over the OBS WDM transmission core. The use of MPLS-type technique for forwarding data bursts and the inclusion of a medium access control layer between the optical (WDM) and IP layers are the key ingredients of the proposed architecture. In particular, the architecture is based on provisioning MPLS paths, also called label switched paths, of desired quality of service through the OBS WDM transmission core. The MAC layer performs various OBS-specific functions, such as burst assembly, burst scheduling, and offset setting/traffic shaping. While burst assembly and burst scheduling are relatively straightforward, we point out that the offset setting strategy has significant impact on the performance of IP network operating over OBS WDM core. We describe a shaping scheme to set the offset, an important system parameter for OBS, between the successive data bursts of a given data stream (label switched path) and their associated control packets. This scheme results in robust operation of the network and also facilitates traffic engineering. Guidelines are provided for implementing various IP QoS mechanisms in the optical backbone using OBS.